Exploring English Reading Challenges in Southwest Papua EFL Classrooms: The Role of Virtual Learning - Nursalim, Nursalim; Nurteteng, Nurteteng; Sari, Galuh Novita; Ayuningtyas, Puteri Nafdila; Yanwarin, Elisabeth (English Education Department, 2024)
This research explores the obstacles students encounter during English reading instruction through virtual learning in Southwest Papua's English as a Foreign Language (EFL) classrooms. The study was conducted at UNIMUDA Sorong, utilizing both offline and online methods for data collection. The researcher recruited 20 participants through convenient sampling. Qualitative data was collected and analysed thematically, revealing that students perceive virtual learning as highly beneficial for improving their English reading skills. They find it user-friendly and hold a positive attitude towards its integration into learning. Consequently, it is asserted that students' favorable perceptions of virtual learning's value in enhancing EFL classrooms in Papua correspond to their adeptness in utilizing virtual learning for reading comprehension. The findings suggest that virtual learning can effectively support EFL instruction, highlighting its potential to overcome traditional learning barriers in this context. Additionally, the study emphasizes the need for adequate technological infrastructure and continuous training for both students and teachers to maximize the benefits of virtual learning.